Musculoskeletal Disorders Associated With Quality of Life and Body Composition in Urban and Rural Public School Teachers - Vega-Fernández, Gustavo; Lera, Lydia; Leyton, Bárbara; Cortés, Pilar; Lizana, Pablo A. (Frontiers in Public Health, 2021)
Introduction: Teachers have been reported to be a labor group with high rates of musculoskeletal disorders (MSD), stress, and strong deterioration of quality of life (QoL). However, little information exists about the association between MSD, QoL, and body composition in rural and urban teachers. Objective: Study the association of MSD with QoL perception and body composition of urban and rural teachers. Participants and Methods: Participants are comprised of a representative sample of urban and rural public schoolteachers from the Valparaiso Region, Chile. MSD were evaluated with the Standardized Nordic Questionnaire for Musculoskeletal Symptoms validated for the Chilean population. QoL perception was evaluated with survey SF-36. Body composition was measured via bioimpedance. A logistic regression model was used to evaluate the association between MSD, QoL and body composition, adjusted for age and gender. Results: A total of 88.9% (urban 90%; rural 87%) of teachers felt pain in some body area, 71.2% of them with limitations. 39% of teachers presented body fat obesity, with the highest rate in rural women. The body area with greatest MSD prevalence was the neck and shoulders (68.6%). Significant differences were observed between teachers with >p75 of MSD (over 6 pain regions) and those with ≤p75 (6 or fewer painful regions; p<0,05) on 6 QoL scales and in physical health components (PCS) and mental health (MCS) in urban teachers. However, rural teachers presented no differences. The association between teachers with >p75 MSD and low QoL perception was significant (p<0.05) in PCS and MCS. Furthermore, the regression model presents a significant association between urban areas and low PCS perception. Conclusions: Urban and rural teachers present high rates of MSD and obesity. Teachers with higher rates of MSD have their mental and physical QoL affected, making workplace intervention in MSD necessary to prevent teacher health deterioration.